Development and Marketing of Solar Innovations: A Case Study - Wirtz, Harald; Janssen, Markus (Journal of Technology Management & Innovation, 2010)
This study aims to examine the process of development and marketing of CIS technology as a major innovation in solar technology through the case of Würth Solar GmbH Co. KG., which is the first company worldwide to have started mass production of CIS-solar modules. This article reports the development history of the technology and analyzes its innovative content. It also describes cooperation with innovation partners as a key to success. The participating organizations and actors involved are shown and their roles in the innovation process are illustrated. Challenges and oppositions are explained and the way the company managed to overcome these difficulties is presented.